Analisis Efisiensi Operasional dan Kepatuhan Syariah pada Layanan Investasi Syariah di Aplikasi Ajaib - Eka Heryani; Dini Selasi (STIKes Ibnu Sina Ajibarang, 2025)
Shariah-compliant investments follow Islamic principles, such as the prohibition of riba, gharar, and maysir, which emphasize fairness and transparency. In the digital era, apps like Ajaib utilize technology to improve efficiency and ensure sharia compliance. This research analyzes the efficiency and sharia compliance of the Ajaib app using a literature study, as well as secondary data from journals, sharia regulations, and official Ajaib documents. The analysis was conducted using a content analysis approach to evaluate the suitability of application features with sharia principles. The results showed that Ajaib has excellent features, such as education, magic bag, stop loss, take profit, and advance charting, which support efficient investment. The stock screener and speed order book features assist users in making quick decisions, while DSN-MUI-certified Islamic mutual funds ensure halal investments. The fast and transparent transaction process makes Ajaib easy to use and compliant with sharia principles. However, the analysis also found some shortcomings, such as a limited selection of Islamic mutual funds, less varied payment methods, and the absence of personalized consultation services. Compared to other apps, Ajaib needs to improve these shortcomings to be more competitive. This study concludes that operational efficiency and sharia compliance are critical to the sustainability of sharia investment in Indonesia. Further research is recommended to examine the user experience directly and compare Ajaib's performance with other platforms.